Utilization Review (Preadmission) Dental Services Before And After Implementation Online Referral System - Erdianto Setya Wardhana; Sandy Christiono; Muhammad Husnun Niam; Dinda Nabila Sukma (Jurusan Keperawatan Gigi, Poltekkes Kemenkes Semarang, 2022)
Problem statement : The online tiered referral system is a digitalized referral system which has been implemented since October 1, 2018. The objective of this research is to find a general overview of the dental and oral health services in the era of national health insurance, before and after the online tiered referral system is implemented by looking at the diagnoses of Social Security Administrator for Health patients at Raden Mattaher Regional Hospital in Jambi Province. Method : Descriptive analytic research was conducted in this research by analyzing preadmission form and referral data of Social Security Administrator for Health patients at Raden Mattaher Regional Hospital in Jambi Province, which were received before and after the implementation of online tiered referral system. Results : Based on the distribution of patient referral data that came to Raden Mattaher Regional Hospital, it was shown that the number before the implementation was higher compared to after, with a total of 135 referrals and 85 referrals. In addition, the value of p 0.05 showed that there was no effect of the online tiered referral system on dental and oral health services at Raden Mattaher Regional Hospital which had been tested by SPSS Paired T-test with a significance value of 0.311 ( 0.05). Conclusion : The conclusion of this research is that the implementation of the online tiered referral system does not affect the dental and oral health services, especially in Raden Mattaher Regional Hospital in Jambi Province Keyword : Online Tiered Referral System; Utilization Review; Preadmission Certification